ANALISIS NILAI SETTING POINT RELE DIFERENSIAL SEBAGAI PROTEKSI TRANSFORMATOR GT UNIT 1 DI PT PLN NUSANTARA POWER UP PAITON - Fatahillah, Muhammad; Dhofir, Moch.; Nurwati, Tri (Jurnal Mahasiswa TEUB, 2024)
Power plants are an important component in a country's electricity system which is responsible for producing large amounts of electrical energy to meet the needs of society, industry and other sectors. There are many types of power plants in Indonesia, one of which is the Steam Power Plant (PLTU). In a PLTU there are electrical components that must be safe when a disturbance occurs. The power transformer is one of the vital electrical components in a PLTU which requires a good protection system so that it can operate optimally. PT PLN Nusantara Power UP Paiton Unit 1 has many power transformers installed, one type of which is the GT Transformer. This transformer works to increase the voltage from 18.25 kV to a voltage of 500 kV. On the GT transformer, there is also one of the protection relays installed, namely the differential relay. However, the existence of the installed differential relay needs to be evaluated, namely not only with mathematical calculations but also with ETAP simulations. In this research, mathematical analysis was carried out by calculating the setting point value and slope range of the differential relay on the GT transformer. After that, a simulation was carried out using ETAP. Based on the results of mathematical analysis and simulation, it shows the consistency of short circuit current values, namely with an average error difference of 1,25% for the primary side and 1.183% for the secondary side. Meanwhile, there are differences in the slope values determined by PLN Nusantara Power and the results of mathematical calculations, namely 9.06% for slope 1 and 18.138% for slope 2 based on mathematical calculations and 20% for slope 1 and 80% for slope 2 based on party settings. PLN Nusantara Power. This difference is caused by consideration of the potential for saturation in the Current Transformer due to excessive loading on the secondary side. This CT saturation condition cannot be detected as a disturbance, so it must be located in the no-trip area. Then, the setting current value based on mathematical calculations and PLN Nusantara Power's settings is also not at 0 A. This is due to consideration of the differential relay sensitivity of 30% which causes the setting current value to be around 0.3 A. Finally, in the curve plot Differential relay characteristics, the average fault point is in the trip area except for 3 phase and secondary side interphase faults which are above the trip area or called instantaneous area. The location of the fault point in this instantaneous area is influenced by the large 3-phase short circuit current value on the GITET side so that it accumulates on the 500 kV bus (secondary side). Keywords— Power Transformer, Differential Relay, Setting Point, ETAP, Characteristic Curve